2011
DOI: 10.1152/ajprenal.00073.2010
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-modified human embryonic mesenchymal stem cell implantation enhances protection against cisplatin-induced acute kidney injury

Abstract: The implantation of mesenchymal stem cells (MSC) has been reported as a new technique to restore renal tubular structure and improve renal function in acute kidney injury (AKI). Vascular endothelial growth factor (VEGF) plays an important role in the renoprotective function of MSC. Whether upregulation of VEGF by a combination of MSC and VEGF gene transfer could enhance the protective effect of MSC in AKI is not clear. We investigated the effects of VEGF-modified human embryonic MSC (VEGF-hMSC) in healing cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 50 publications
4
74
1
1
Order By: Relevance
“…The survival rate on day 28 was significantly higher in the NAChMSC group (83.3%) than in either the Bleo group (40.0%) or the hMSC group (60.0%). Similar to our previous experiments with hMSCs, 26 there was no evidence of tumor formation in any of the surviving nude mice 2 months after cell injection.…”
Section: The Effects Of Nac-hmscs On Reducing the Mortality Of Mice Wsupporting
confidence: 89%
“…The survival rate on day 28 was significantly higher in the NAChMSC group (83.3%) than in either the Bleo group (40.0%) or the hMSC group (60.0%). Similar to our previous experiments with hMSCs, 26 there was no evidence of tumor formation in any of the surviving nude mice 2 months after cell injection.…”
Section: The Effects Of Nac-hmscs On Reducing the Mortality Of Mice Wsupporting
confidence: 89%
“…No tumorigenesis was observed in previous studies using hMSC and vascular endothelial growth factor-modified hMSC to treat acute kidney injury in nude mice. 19 The safety of using hMSC in the treatment of MRL/Lpr mice was also confirmed in our study, knowing that no tumorigenesis was observed three months after hMSC grafting.…”
supporting
confidence: 79%
“…To address this problem, a number of studies aimed at promoting the retention and survival of MSCs to increase the number of cells successfully engrafting in the injured kidney have been published. The main strategy utilized has involved the alteration of ‘seeds' meaning donor cells by preconditioning or genetic modification of MSCs [24,25,26]. However, these techniques do not always provide sufficient effects for the improvement of the cell survival, and further exploration is required for clinical application due to the complexity of these procedures.…”
Section: Discussionmentioning
confidence: 99%